2022
DOI: 10.1007/s42114-022-00535-x
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-like CoMoP2/MoP heterostructures coupling N, P co-doped carbon nanosheets as advanced anodes for high-performance lithium-ion batteries

Abstract: Transition-metal phosphides as ideal anodes have been attracted a large number of interests due to their excellent performance for lithium-ion batteries. Nevertheless, CoMoP 2 materials were rarely reported as lithium-ion battery anode materials. Thereupon, to excavate their ability in LIBs, a sandwich-like architecture was employed as anode material, in which heterostructured CoMoP 2 and MoP nanoparticles were coated on N, P co-doped carbon matrix. Notably, doped carbon micro-lamellated sheets could not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 64 publications
2
43
0
Order By: Relevance
“…The data showed that the specific surface area of the PANI microtubes is more significant than that of ordinary PANI nanoparticles, which is related to its hollow microtube structure, indicating its potential application in electronic materials requiring a high specific surface area. 60,61 3.5. Dispersibility of Polyaniline Microtubes.…”
Section: Optimization Of the Conductivity Of Polyaniline Microtubesmentioning
confidence: 99%
“…The data showed that the specific surface area of the PANI microtubes is more significant than that of ordinary PANI nanoparticles, which is related to its hollow microtube structure, indicating its potential application in electronic materials requiring a high specific surface area. 60,61 3.5. Dispersibility of Polyaniline Microtubes.…”
Section: Optimization Of the Conductivity Of Polyaniline Microtubesmentioning
confidence: 99%
“…Compared with the previously reported catalysts, the data suggest that the P1a-MNP and P2a-MNP can act as efficient catalysts as they have a vast surface area. 68,69 The high surface area of the catalyst is favorable for the adsorption of reactants as a more significant number of active sites are on the surface.…”
Section: Tnbs Assaymentioning
confidence: 99%
“…Due to the high efficiency and low cost of composite nanomaterials, most researchers have focused on the photocatalytic technology of using composite nanomaterials to treat wastewater and degrade pollutants in water. 35–37…”
Section: Introductionmentioning
confidence: 99%